2020
DOI: 10.1016/j.jaac.2019.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Nonmedical Use of Prescription Stimulants: Risk Factors, Outcomes, and Risk Reduction Strategies

Abstract: Objective: To review all literature on the nonmedical use (NMU) and diversion of prescription stimulants to better understand the characteristics, risk factors, and outcomes of NMU and to review risk-reduction strategies. Method: We systematically searched PubMed, PsycINFO, and SCOPUS from inception to May 2018 for studies containing empirical data about NMU and diversion of prescription stimulants. Additional references identified by the authors were also assessed for inclusion. Results: A total of 111 studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
119
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 114 publications
(320 reference statements)
7
119
0
6
Order By: Relevance
“…The increase in ADHD medication prescription in the UK over the last two decades has been a cause of national concern, provoking responses from health and educational representatives (36,37). Concerns have also been expressed around the potential diversion and misuse of ADHD medication as a "study drug" (38). This leads to short-sighted calls to curtail prescriptions, but risks unfairly penalizing those who genuinely need ADHD medication.…”
mentioning
confidence: 99%
“…The increase in ADHD medication prescription in the UK over the last two decades has been a cause of national concern, provoking responses from health and educational representatives (36,37). Concerns have also been expressed around the potential diversion and misuse of ADHD medication as a "study drug" (38). This leads to short-sighted calls to curtail prescriptions, but risks unfairly penalizing those who genuinely need ADHD medication.…”
mentioning
confidence: 99%
“…While students’ motive to use prescription stimulants nonmedically for better performance while studying has been frequently reported in student samples of different ages (Faraone et al, 2020; Garnier-Dykstra et al, 2012; Rabiner et al, 2009; Schepis et al, 2020; Teter et al, 2020), parents’ willingness to initiate such behavior and the etiology behind their decision-making have rarely been studied. To the best of our knowledge, this is the first set of theory-driven research experiments investigating parents’ willingness to give CE to healthy children and the question of the drivers that lead parents to do so.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent systematic review of nonmedical prescription stimulant use found already 111 studies meeting the inclusion criteria (23). But just like Smith and Farah before, Faraone and colleagues found much variance between the publications in terms of definitions used to investigate nonmedical use, methodologies, and samples, which made a formalized meta-analysis impossible.…”
Section: Prevalence Studiesmentioning
confidence: 99%
“…Summarizing all the data, males, 18-25 year-olds, whites, fraternity/sorority members, students with worse grades, people who had been binge drinking in the last month, had used marijuana or nonprescription stimulants (e.g. MDMA or methamphetamine) in the past year, had had adverse childhood experiences, and have not grown up with both biological parents were most likely to use prescription stimulants (23). The authors conclude that this use is a significant public health problem, but that it has not reached epidemic proportions like nonmedical opioid use in the United States.…”
Section: Prevalence Studiesmentioning
confidence: 99%